(untitled) (Baghdad Science Journal, 2008)
Two isolates of Staphylococcus xylosus (urease producer and non urease producer) were injected in mice at a dose of 2 × 108 colony-forming units (CFU) intraurethrally. Results showed that both isolates were able to colonize kidney and bladder of the injected mice, regardless of their urease production. Moreover, there were insignificant differences between the two groups. These results emphasized the pathogenicity of this bacteria in UTI.